2013
DOI: 10.1007/s10461-013-0450-z
|View full text |Cite
|
Sign up to set email alerts
|

Which Gay Men Would Increase Their Frequency of HIV Testing with Home Self-testing?

Abstract: Many Australian gay men do not get tested for HIV at the recommended frequency. Barriers to HIV testing may be reduced by the availability of home HIV self-testing (HHST). An online cross-sectional questionnaire was conducted with 2,306 Australian gay men during 2009. Multivariate logistic regression identified factors associated with being likely to increase testing frequency if HHST was available, among previously-tested and never-tested men. Among 2,018 non-HIV-positive men, 83.9% had been tested. Two-third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 34 publications
6
74
1
Order By: Relevance
“…Taking into account the French findings and the fact that for the MSM attendees of our study, being in favor of self-test authorization was associated with no one knowing about their sexual relations with men (a characteristic we presume to be more common outside large cities characterized by high gay visibility), this current study probably underestimates the percentage being in favor and with potential lead time in the global Spanish population level at risk of being infected by HIV. We did not ask about the intention of increasing the frequency of testing as other studies did [44,47]; the current study chose not to focus in potential future use, but to ask about the potential previous use to advance the current test, since this option was considered a more direct indicator of potential use. The almost six month lead time per participant could be considered a valuable measure of impact, taking into account that this is a population level measure.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the French findings and the fact that for the MSM attendees of our study, being in favor of self-test authorization was associated with no one knowing about their sexual relations with men (a characteristic we presume to be more common outside large cities characterized by high gay visibility), this current study probably underestimates the percentage being in favor and with potential lead time in the global Spanish population level at risk of being infected by HIV. We did not ask about the intention of increasing the frequency of testing as other studies did [44,47]; the current study chose not to focus in potential future use, but to ask about the potential previous use to advance the current test, since this option was considered a more direct indicator of potential use. The almost six month lead time per participant could be considered a valuable measure of impact, taking into account that this is a population level measure.…”
Section: Discussionmentioning
confidence: 99%
“…A second Excel data extraction "checklist", formulated from the 2015 TGA's clinical performance requirements for HIVST kits and Medical Device Essential Principles Checklist (Therapeutic Goods Administration, 2015a, 2015c) and outcomes of a literature review of international and Australian studies exploring what consumers and service providers consider the "ideal" information to accompany a HIVST kit (Bavinton et al, 2013;Krause, Subklew-Sehume, Kenyon, & Colebunders, 2013;Ng et al, 2012;Yang et al, 2014), was used to assess the content of the received kits and accuracy of the accompanying information. Table 1 shows the characteristics of the nine websites offering HIVST for purchase and delivery to Australia identified in each search round.…”
Section: Methodsmentioning
confidence: 99%
“…HIVST devices have been available in the United States (US) since 2012 (Food and Drug Administration, 2014) and early 2014 in the United Kingdom (Allais & Venter, 2014;Pebody, 2015). Mathematical modelling (University of New South Wales and St Vincent's Centre for Applied Medical Research HIV Home Testing Assessment Group, 2015) and early evidence (Bavinton et al, 2013;Chen et al, 2010) support HIVST as a means of increasing Australian testing rates. However, despite the Australian Therapeutic Goods Administration (TGA) lifting supply restrictions in July 2014 (Therapeutic Goods Administration, 2014, 2015a, 2015b, HIVST kits remain off-market in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Pilot studies in Malawi and Kenya have demonstrated generally high acceptability among health workers and the general populations [11,12], along with high accuracy of self-testing with HIV RDTs that use oral fluid, when combined with a demonstration step and illustrated instructions [11,16,17]. In the USA, France and Australia, acceptability of targeted HIVST is reportedly high among men who have sex with men [19][20][21]. There have been only limited studies on unsupervised HIVST in resource-limited settings [8,12].…”
mentioning
confidence: 99%